2022
DOI: 10.1007/s10935-022-00709-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Transdiagnostic Universal Prevention Program on Anxiety in Junior High School Students After School Closure During the COVID-19 Pandemic

Abstract: School closures due to the coronavirus disease 2019 (COVID-19) pandemic have worsened mental health problems for children and adolescents worldwide. We aimed to examine the follow-up effectiveness of a transdiagnostic universal prevention program for anxiety of junior high school students after a nationwide school closure during the COVID-19 outbreak in Japan. A total of 117 junior high school students were included in the analysis. We used the Unified Universal Prevention Program for Diverse Disorders (Up2-D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…As far as within-group comparisons for the PROCARE condition, signi cant differences were found in most variables between the pre-treatment and the 12month follow-up, with similar results to those found after the completion of the main treatment (30) and providing evidence for the promising previous studies of the transdiagnostic approach for young people for clinical and universal prevention (23,28,54). This maintenance of treatment effects in PROCARE contrasts with studies which have found that prevention treatment improvements decline over time (53).…”
Section: Discussionsupporting
confidence: 74%
“…As far as within-group comparisons for the PROCARE condition, signi cant differences were found in most variables between the pre-treatment and the 12month follow-up, with similar results to those found after the completion of the main treatment (30) and providing evidence for the promising previous studies of the transdiagnostic approach for young people for clinical and universal prevention (23,28,54). This maintenance of treatment effects in PROCARE contrasts with studies which have found that prevention treatment improvements decline over time (53).…”
Section: Discussionsupporting
confidence: 74%
“…This may partially explain why very young children were not included. The age range varied between studies, with some including children within a 2-year age range and others including a large age range [ 14 , 21 , 27 , 38 ]. For studies that reported sex, females were included at slightly higher percentages than males (overall, 5284/8383 = 63%).…”
Section: Resultsmentioning
confidence: 99%
“…With high school students, the Unified Universal Prevention Program for Diverse Disorders was implanted during the COVID-19 pandemic to help students with their anxiety (Kishida et al, 2023). The intervention addressed several themes related to mental health, such as social skills training, relaxation, exposure, problem-solving and cognitive restructuring.…”
Section: The Contribution Of the School Setting And The Impact Of Uni...mentioning
confidence: 99%